Full issue file A REVIEW OF CHEMICAL ENGINEERING EDUCATION: PAST, PRESENT AND FUTURE DIRECTIONS IN IRAN AND THE WORLD - Mohammad Soltanieh; Rahbar Rahimi; Toraj Mohammadi; Seyed Nezameddin Ashrafizadeh; Soheil Zarghami (آموزش مهندسی ایران)
In this paper, after a brief investigation of the history of chemical engineering in Iran and the world, the published papers related to chemical engineering education in the Iranian Journal of Engineering Education, on the occasion of its 25th anniversary of publication, were reviewed. In educational part of the present work, the novel educational methods such as remote education, e-learning, game-based education, virtual reality education and the outcomes of these methods are discussed. In addition, from the research perspective, the latest directions of chemical engineering such as stimuli-responsive polymeric micelles, drug delivery, cancer therapy, antimicrobial active packaging films, active food packaging, advanced electro spun nanofiber yarn-based textiles, wound healing applications, advanced technologies for water and wastewater treatment, application of nanomaterials and ionic metals, green and renewable energies, and the applications of artificial intelligence in chemical engineering were reviewed. From the foresight vision and considering the global changes such as environmental challenges, limited world resources, the novel areas of chemical engineering and its future, with emphasis on chemical engineering education, have been investigated. With progresses in many interdisciplinary areas such as energy and decarbonization, water, food, air, human health and medicine, it is being expected that great changes occur in the education of chemical engineering.